Bibliometric analysis for global marine microplastic pollution control from 2013 to 2022 - Lou, Xiaoyi; Sui, Yifan; Fang, Changling; Tang, Yunyu; Huang, Dongmei; Guo, Yaoguang (Frontiers in Environmental Science, 2023)
The control of microplastic pollution in the marine environment has become a growing public concern in recent years. To better grasp the trends and development of microplastic pollution control in the marine environment, the published literature in Science Citation Index Expanded (SCIE) database of Web of Science Core Collection from 2013 to 2022, up to a total of 2357 articles or reviews was analyzed through CiteSpace and VOSviewer tools. The results show an exponential growth in the number of papers related to the control of microplastic pollution in the marine environment, with China, USA, India and Australia providing the main drivers, while China being the most active country, with Science of the Total Environment, Marine Pollution Bulletin, Environmental Pollution and Chemosphere being the most important sources for publishing relevant research. A relatively complete theoretical framework has been developed for the control of marine microplastic pollution, focusing on the quantification, traceability and collectability of microplastics. However, few papers have focused on policy implications and technological innovations in this area. The research on marine microplastic pollution control has transitioned from traceability and hazard analysis of microplastics to the impact of economic activities and synthetic fibre on microplastic pollution. Microplastics in wastewater discharged from municipal wastewater treatment plants, human consumption, man-made fibers and synthetic polymers have become the frontier of research. The present study is of significance for better understanding and supporting further research on the control of microplastic pollution in the marine environment.